The effects of a cash transfer intervention on sexual partnerships and HIV in the HPTN 068 study in South Africa. Issue 10 (2nd October 2020) - Stoner, Marie C. D.; Kilburn, Kelly; Hill, Lauren M.; MacPhail, Catherine; Selin, Amanda; Kimaru, Linda; Khoza, Nomhle; Hove, Jennifer; Twine, Rhian; Kahn, Kathleen; Pettifor, Audrey
Abstract: Evidence on cash transfer interventions for HIV prevention in adolescent girls and young women is unclear and indicates that they may not work uniformly in all settings. Qualitative interviews were conducted with 22 girls and young women post-intervention to determine how a cash transfer study (HPTN 068) in South Africa was perceived to influence sexual behaviours and to explore mechanisms for these changes. Participants described how the intervention motivated them to increase condom use, have fewer partners, end risky relationships and access HIV testing services at local primary health clinics. Changes were attributed to receipt of the cash transfer, in addition to HIV testing and sexual health information. Processes of change included improved communication with partners and increased negotiation power in sexual decision-making. Economic empowerment interventions increase confidence in negotiating behaviours with sexual partners and are complementary to sexual health information and health services that provide young women with a foundation on which to make informed decisions about how to protect themselves.